PGF2α facilitates pathological retinal angiogenesis by modulating endothelial FOS‐driven ELR+ CXC chemokine expression - Yan Zhao; Yi Lei; Huying Ning; Yaqiang Zhang; Guilin Chen; Chenchen Wang; Qiangyou Wan; Shumin Guo; Qian Liu; Ruotian Xie; Yujuan Zhuo; Shuai Yan; et al. (EMBO Molecular Medicine)
Abstract The pathological retinal angiogenesis often causes blindness. Current anti‐angiogenic therapy for proliferative retinopathy targets the vascular endothelial growth factor (VEGF), but many patients do not radically benefit from this therapy. Herein, we report that circulating prostaglandin (PG) F2α metabolites were increased in type 2 diabetic patients with proliferative retinopathy, and the PGF2α receptor (Ptgfr) was upregulated in retinal endothelial cells (ECs) from a mouse model of oxygen‐induced retinopathy (OIR). Further, disruption of the PTGFR receptor in ECs attenuated OIR in mice. PGF2α promoted the proliferation and tube formation of human retinal microvascular endothelial cells (HRMECs) via the release of ELR+ CXC chemokines, such as CXCL8 and CXCL2. Mechanistically, the PGF2α/PTGFR axis potentiated ELR+ CXC chemokine expression in HRMECs through the Gq/CAMK2G/p38/ELK‐1/FOS pathway. Upregulated FOS‐mediated ELR+ CXC chemokine expression was observed in retinal ECs from PDR patients. Moreover, treatment with PTGFR inhibitor lessened the development of OIR in mice in a CXCR2‐dependent manner. Therefore, inhibition of PTGFR may represent a new avenue for the treatment of retinal neovascularization, particularly in PDR.